Women Hospitalized for Acute on Chronic Decompensated Systolic Heart Failure Receive Less Furosemide Compared to Men - Tyler P. Rasmussen; Noah N. Williford; Christopher DeZorzi; Aziz Hammoud; Brenden J. Boyle; Yunshu Zhou; Patrick Ten Eyck; Milena A. Gebska (Cardiology Research and Practice)
The cumulative incidence of systolic heart failure is similar in men and women. However, major prognostic differences exist between genders. We sought to measure gender differences in furosemide prescribing patterns for patients with preexisting heart failure with reduced ejection fraction (HFrEF) admitted with Stage C acute decompensation, regardless of the underlying cause. We conducted a single-center retrospective analysis of patients admitted between 2015 and 2018 for acute on chronic decompensated HFrEF. Primary outcomes were differences in initial furosemide dose, total dose over the first 24 hours of hospitalization, and total dose during the entire hospitalization between women and men. Secondary outcomes included acute kidney injury (AKI), intubation, noninvasive ventilation (NIV), and in-hospital 30-day and 1-year mortality. We studied 434 patients (31% female) with similar baseline characteristics. Females received significantly less furosemide compared to men for the initial dose, over the first 24 hours, and throughout their hospitalization. However, AKI was more prevalent in women versus men (p=0.008). Females admitted for acute on chronic decompensated HFrEF receive significantly less furosemide when compared to men, but developed more AKI prior to discharge.